A Protein Microarray Analysis of Plasma Proteins for the Prediction of Spontaneous Preterm Delivery in Women with Preterm Labor - Hong, Subeen; Park, Kyo Hoon; Kim, Yu Mi; Lee, Young Eun; Park, Yehyon; Lee, Ji Eun (SAGE Publications, 2020)
We aimed to identify novel biomarkers in maternal plasma that predict spontaneous preterm delivery (SPTD) in women with preterm labor (PTL) using an antibody microarray and to develop the best prediction model for SPTD based on these biomarkers in combination with clinical and ultrasound factors. This retrospective cohort study included 215 women with singleton pregnancies and PTL (23-33 weeks) who gave plasma samples. In a nested case-control study design, plasma proteomes from SPTD (case subjects, n = 15) and term delivery (control subjects, n = 15) groups were differentially profiled using a membrane-based antibody microarray. Six candidate biomarkers of interest were validated by enzyme-linked immunosorbent assay (ELISA) in the total cohort (n = 215). Cervical lengths were also measured. The primary outcome measure was SPTD within 48 h after sampling. Twenty of the molecules studied displayed significant intergroup differences. Validation by ELISA confirmed significantly higher levels of plasma endostatin and lipopolysaccharide binding protein (LBP) in women who had SPTD within 48 h than in those delivering after 48 h. However, plasma macrophage inflammatory protein (MIP)-1 alpha levels were significantly lower in women who delivered within 48 h. A combined model was developed to predict SPTD within 48 h using a stepwise regression procedure, which included plasma endostatin and LBP levels, nulliparity, and cervical length (area under the curve = 0.920). Plasma LBP, endostatin, and MIP-1 alpha are potential new biomarkers for predicting imminent SPTD and a combined noninvasive model based on these biomarkers and clinical and ultrasound factors can accurately predict imminent SPTD in women with PTL.